2010
DOI: 10.1007/s10549-010-0742-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between TA-repeat polymorphism in the promoter region of UGT1A1 and breast cancer risk: a meta-analysis

Abstract: Uridine diphospho-glucuronosyltransferase 1A1 (UGT1A1) plays an important role in breast cancer development. To date, many publications have evaluated the correlation between UGT1A1 TA-repeat polymorphism and breast cancer risk. However, the results remain inconclusive. In order to resolve this conflict, a meta-analysis was performed by searching Medline, PubMed, and ISI Web of Knowledge databases. Seven studies including 5,746 cases and 8,365 controls were collected for UGT1A1 TA-repeat polymorphism. The stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Furthermore, one study showed a decreased risk of UGT1A1*28 for breast cancer in Nigerian women (Huo et al 2008). A meta-analysis study published in 2010 (Yao et al 2010), which aggregated 5,746 cases and 8,365 controls from most of these studies, concluded that there was evidence for enhanced risk for breast cancer in Caucasian women with the UGT1A1*28 allele. Consequently our finding of lower BPA glucuronidation in breast tissue with the UGT1A1*28 may explain in part these observations of enhanced breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study showed a decreased risk of UGT1A1*28 for breast cancer in Nigerian women (Huo et al 2008). A meta-analysis study published in 2010 (Yao et al 2010), which aggregated 5,746 cases and 8,365 controls from most of these studies, concluded that there was evidence for enhanced risk for breast cancer in Caucasian women with the UGT1A1*28 allele. Consequently our finding of lower BPA glucuronidation in breast tissue with the UGT1A1*28 may explain in part these observations of enhanced breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…We selected polymorphisms that were associated with breast cancer risk in some, but not all, studies. The following polymorphisms were genotyped: SHBG rs6259 [5], [8], [18], [19], [20]; PGR rs1042838 [11], [20], [21], [22], [23], [24], [25]; ESR1 rs2234693 [20], [26], [27], [28], CYP19 rs10046 and rs4775936 [5], [7], [20], [29], [30], [31], [32], [33]; and UGT1A1 rs8175347 [34], [35], [36], [37], [38], [39].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results from our study did not indicate a correlation between the UGT1A1*28 polymorphism and breast cancer risk. Such controversial results have also been reported by previous studies and are speculated to result from inter-ethnic and regional variations in the UGT1A1*28 polymorphism (Kaniwa et al, 2005;Yao et al, 2010). For example, the frequency of homozygous and heterozygous UGT1A1*28 genotypes is approximately 10-15 and 35-50%, respectively, in Caucasians (Beutler et al, 1998;Innocenti et al, 2002).…”
Section: Discussionmentioning
confidence: 63%
“…A previous study involving 200 African American women with breast cancer and 200 healthy controls demonstrated a strong association between the incidence of breast cancer and the UGT1A1*28 polymorphism, and a stronger association between this incidence and menopause and ER status (Guillemette et al, 2000). However, this association was not observed in a Chinese population (Adegoke et al, 2004;Yao et al, 2010). Further stratification by age showed a correlation between the UGT1A1*28 risk allele and a slight elevation in breast cancer risk in Chinese women less than 40 years of age (Adegoke et al, 2004).…”
Section: Introductionmentioning
confidence: 79%